Antioxidative and lipid-reducing activities of Ficus deltoidea in palmitic acid-induced WRL68 cells / Noor Nazirahanie Abrahim - Noor Nazirahanie, Abrahim (2021)
Non-alcoholic fatty liver disease (NAFLD) is a series of liver disorder caused by deposition of fat without involving alcohol. This chronic liver disease has become a major concern globally due to its high mortality and morbidity rate. This situation leads to the quest of finding natural remedy to overcome this condition. Ficus deltoidea or commonly known as mistletoe fig or Mas Cotek, is a plant that is very well known especially in Malaysia for its blood glucose lowering effect. However, the potential value of F. deltoidea has not been fully evaluated, and no studies have been published on the effects of F. deltoidea on NAFLD. Therefore, the aim of this study is to determine the potential effect of F. deltoidea leaves on the improvement of NAFLD especially on lipid accumulation using cultured cell model. Leaves from three varieties of F. deltoidea, colloquially termed small-(FDS), medium-(FDM), and big-type leaf (FDB), were subjected to water extraction. The crude (C) extracts were fractionated using water (WF) and ethyl acetate (EAF). The phenolic and flavonoid content, antioxidant activity, and cytotoxicity of the fractions were investigated. Due to its high phenolic content, antioxidant activity was highest in the FDB crude water extract, especially on metal chelating, inhibition of lipid peroxidation, LDL oxidation and HMG-CoA reductase activities. Through MTT assay, none of the samples showed cytotoxicity towards WRL68 cell line. Subsequently, palmitic acid (PA) was used to induce lipid accumulation (steatosis) in WRL68 cells, and all the samples were tested for their lipid reducing activity by using two different protocols i.e., pre-, and post-treatments. Only FDB shows lipid reduction at the highest tested concentration (200 µg/ml) and were used for subsequent experiment. Pre-treatment with FDB was found to restore redox status by increasing SOD and GPx level, and less malondialdehyde (MDA) formation. The iv changes in protein expressions were studied by using proteomic approaches via 2DE separation followed by identification of protein spots of interest using MALDIMS/MS. Six proteins were successfully identified which are HSPB1, PSMA1, GSTO1, PRDX1, HIST1H2BD and UCHL3. Through bioinformatics analysis, these proteins were found to be significantly involved in specific pathways such as oxidative stress (PRDX1 and GSTO1), protein homeostasis (HSPB1) and degradation (UCHL3 and PSMA1). Meanwhile, phytochemical analysis of crude water extract of FDB using ultra high-performance liquid chromatography (UHPLC), reveals the presence of flavone (vitexin) and phenolic acid (p-coumaric acid). Based on the data, the polyphenolic-rich extract of F. deltoidea might have the potential to reduce lipid levels due to the presence of phenolic compounds with high antioxidant activities. Results obtained suggest that this Malaysian herb have a probable preventive effect on chronic liver disease especially in the early stage of NAFLD. Thus, these findings might be helpful to various treatment plans for fatty liver in the future. At the same time, it shows the practice of consuming this plant to be beneficial for health. Keyword : Ficus deltoidea, antioxidant, steatosis, oxidative stress, protein homeostasis